2017
DOI: 10.1007/s10554-017-1138-7
|View full text |Cite
|
Sign up to set email alerts
|

The utility of global longitudinal strain in the identification of prior myocardial infarction in patients with preserved left ventricular ejection fraction

Abstract: Prior myocardial infarction (MI) is associated with increased mortality and is prevalent in certain high risk patient groups. Electrocardiogram may be used in diagnosis, however, sensitivity is limited, thus non-invasive imaging techniques may improve diagnosis. We investigated whether global longitudinal strain (GLS) and longitudinal strain parameters are reduced in patients with prior MI but preserved left ventricular ejection fraction (LVEF). The study included 40 clinical patients with prior MI occurring >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…However, while Ogawa et al (19) showed that MI presence and position could be assessed using both feature tracking and myocardial tagging, the sensitivity and specificity for detecting MI segments were low (feature tracking: sensitivity, 72%; specificity, 71%; tagging technique: sensitivity, 71%; specificity, 75%). Fent et al (34) also reported that feature tracking could identify prior MI but the AUC was low (0.66 [95% CI: 0.54, 0.79], P = .012).…”
Section: Discussionmentioning
confidence: 99%
“…However, while Ogawa et al (19) showed that MI presence and position could be assessed using both feature tracking and myocardial tagging, the sensitivity and specificity for detecting MI segments were low (feature tracking: sensitivity, 72%; specificity, 71%; tagging technique: sensitivity, 71%; specificity, 75%). Fent et al (34) also reported that feature tracking could identify prior MI but the AUC was low (0.66 [95% CI: 0.54, 0.79], P = .012).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal strain is altered in ischemic heart disease, also in cases with preserved EF [14], and represents an early marker of subclinical myocardial contractility dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that CS Reducer may positively affect global left ventricle (LV) systolic function [6][7][8]12], other did not find any modification [13]. Longitudinal strain is known to be altered in acute and chronic heart disease, representing a more sensitive tool than ejection fraction for the evaluation of subclinical alteration of myocardial contractility in ischemic patients [14]. However, the real impact of CS Reducer on myocardial systolic deformation proprieties remains unstudied.…”
Section: Introductionmentioning
confidence: 99%
“…Strain analysis was performed using a cvi42 (v5.1) feature tracking (FT) module in a semi-automated manner (Fig. 2 ; [ 11 ]). FT analysis was done by two observers (GF and PG).…”
Section: Methodsmentioning
confidence: 99%